Relationship between assessment of physical activity with body mass index and maximum oxygen volume in adult men with overweight and obesity - Anang Fajar Aryanto; Damayanti Tinduh; I Putu Alit Pawana Putra; Soenarnatalina Melaniani; Vitria Wuri Handayani (Romanian Medical Journal)
Background. Non-communicable diseases (NCDs) are the leading cause of early adult mortality, often originating in adolescence. Obesity a prevalent NCD, commonly develops during youth and can measured by body mass index (BMI). Objectives. This study was to describe the relationships between physical activity, as defined by the International Physical Activity Questionnaire (IPAQ), BMI, and maximum oxygen consumption (VO2max) in adult men who are overweight or obese. Materials and methods. This descriptive study utilized the IPAQ-SF, BMI, and VO2max data from 22 medical records of adult men who were overweight or obese, selected using a purposive sampling approach. Outcomes. Physical activity and BMI are negatively correlated, with a p-value of 0.000 and a Pearson correlation coefficient of -0.989. Statistical significance is indicated by the p-value of 0.000, and the Pearson correlation coefficient of 0.884 shows a strong positive association between VO2max and physical activity. BMI and VO2max are negatively correlated, with a p-value of 0.000 and a Pearson correlation coefficient of -0.896. Conclusion. The study indicates a relationship between physical activity and BMI, as well as between physical activity and VO2max. Additionally, there is a relationship between BMI and VO2max. Overall, physical activity, BMI, and VO2max are interrelated in overweight or obese adult men.